Barriers to making recommendations about medical tests: a qualitative study of European guideline developers. Issue 9 (16th September 2016) - Gopalakrishna, Gowri; Leeflang, Mariska M G; Davenport, Clare; Sanabria, Andrea Juliana; Alonso-Coello, Pablo; McCaffery, Kirsten; Bossuyt, Patrick; Langendam, Miranda W
Abstract : Objectives: Development of medical test guidelines differs from intervention guideline development. These differences can pose unique challenges in building evidence-based recommendations to guide clinical practice. The aim of our study was to better understand these challenges, explore reasons behind them and identify possible solutions. Setting and participants: In this qualitative study, we conducted in-depth interviews between February 2012 and April 2013 of a convenience sample of 17 European guideline developers experienced in medical test guideline development. Outcomes measured: We used framework analysis with deductive and inductive approaches to generate the themes from the interviews. We kept interpretation grounded in the data. Results: Guideline developers acknowledged that inclusion of patient important outcomes in their guideline development was necessary but lacking. This and other challenges raised fell into 3 broad and overlapping domains: methodological issues, resource limitations and a lack of awareness on the need for evidence that links testing to patient outcomes. Education was mentioned as a key solution to increase awareness and address the resources limitations mentioned. Conclusions: Challenges guideline developers face were interlinked across the domains of methodological issues, resource limitations and a lack of awareness. Solutions that addressed these challenges in parallel are needed. Raising awareness, education and training of relevant stakeholders such as medical doctors, funders and regulators to look beyond test accuracy is key to having a long-term resolution to the issues faced in medical test guideline development.